Key Role of Teichoic Acid Net Charge in Staphylococcus aureus Colonization of Artificial Surfaces - Gross, Matthias (American Society for Microbiology, 2001)
Staphylococcus aureus is responsible for a large percentage of infections associated with implanted biomedical devices. The molecular basis of primary adhesion to artificial surfaces is not yet understood. Here, we demonstrate that teichoic acids, highly charged cell wall polymers, play a key role in the first step of biofilm formation. An S. aureus mutant bearing a stronger negative surface charge due to the lack of d-alanine esters in its teichoic acids can no longer colonize polystyrene or glass. The mutation abrogates primary adhesion to plastic while production of the glucosamine-based polymer involved in later steps of biofilm formation is not affected. Our data suggest that repulsive electrostatic forces can lead to reduced staphylococcal biofilm formation, which could have considerable impact on the design of novel implanted materials.